Physical Quality of Broiler Meat Given Synbiotics from Probio_FM and Mannan Oligosaccharides (MOS) in Rations: Synbiotic broiler meet - Pratama, Yayan Yogi; Mairizal, Mairizal; Yusrizal, Yusrizal (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
This research aims to determine the effect of providing synbiotics from Probio_FM and Mannan Oligosaccharides (MOS) in the ration on the physical quality of broiler meat at a certain level. The material used was 200 DOC (Day Old Chick) Lohman strain MB 202 Platinum strains produced by PT Japfa Comfeed. Broilers were maintained for 35 days, this study used 5 treatments and 4 replications, namely P0 (commercial feed + 0% Probio_FM and MOS (Control)), P1 (commercial feed + 0.25% Probio_FM and MOS), P2 (commercial feed + 0 .50% Probio_FM and MOS), P3 (commercial feed + 0.75% Probio_FM and MOS), P4 (commercial feed + 1 % Probio_FM and MOS.  The variables observed were meat pH, cooking loss and water holding capacity (WHC). Data were analyzed using analysis of variance (ANOVA), if there was a significant effect then it was continued with the Duncan test. The results showed that administration of synbiotics from Probio_FM and MOS had no significant effect (p > 0.05) on the physical quality of broiler meat which included pH value, binding capacity. water, and cooking loss. It was concluded that synbiotics from Probio_FM and MOS could be added to the ration without reducing the physical quality of broiler meat.